Information in the revision process of real-time datasets - Valentina Corradi; Andres Fernandez; Norman R. Swanson (Rutgers University, Department of Economics, 2011)
Rationality of early release data is typically tested using linear regressions. Thus, failure to reject the null does not rule out the possibility of nonlinear dependence. This paper proposes two tests that have power against generic nonlinear alternatives. A Monte Carlo study shows that the suggested tests have good finite sample properties.Additionally, we carry out an empirical illustration using a real-time dataset for money, output, and prices. Overall, we find evidence against data rationality for output and prices, but not for money.
Keywords: C32; C53; E01; E37; E47; 330; bias; efficiency; generically comprehensive tests; rationality; preliminary; final; real-time data; Zeitreihenanalyse; Modellierung; Schätztheorie; Theorie